2017
DOI: 10.3917/spub.175.0719
|View full text |Cite
|
Sign up to set email alerts
|

Comprendre le renoncement à la référence obstétricale à la Clinique universitaire de gynécologie et d’obstétrique de Cotonou

Abstract: Referral is generally perceived as necessary in the case of complications during pregnancy, by both referred women and healthcare personnel. However, differences in points of view are observed when the woman is referred to CUGO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Indeed, these many authors have described such systems of “favoritism”, in which the “protected” individuals take advantage of privileged social relationships with caregivers [38 . p 70, 39 , 19 ]. All these elements reinforce the idea that the behavior of health professionals is a central element in patient assessments of health services [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, these many authors have described such systems of “favoritism”, in which the “protected” individuals take advantage of privileged social relationships with caregivers [38 . p 70, 39 , 19 ]. All these elements reinforce the idea that the behavior of health professionals is a central element in patient assessments of health services [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies on perceived quality of care have revealed various forms of obstetric violence (OV). For example, an analysis of relational aspects has highlighted violent interactions between caregivers and patients [ 12 , 14 , 15 , 18 , 19 ] and analyses of organizational aspects have revealed failings in the care offered, such as an absence of pain treatment [ 17 , 20 , 21 ], interventions without consent [ [20] , [21] , [22] ], a lack of intimacy [ 12 , 15 , 17 ], a lack of communication [ 11 ], and long waiting times for consultations [ 18 ]. A mismatch between local registers of disease interpretation and the biomedical or cultural resources on offer [ 17 ] has also been noted and defined as a form of violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation